Cellulose nanofiber isolation from palm oil Empty Fruit Bunches (EFB) through strong acid hydrolysis. (March 2018) - Setyaningsih, Dwi; Uju,; Muna, Neli; Isroi,; Suryawan, Nyoman Budi; Nurfauzi, Ami Azid
Abstract: The palm oil industry produces about 25-26% of palm oil empty fruit bunches. The empty fruit bunch of palm oil contains cellulose up to 36.67%. This is a good opportunity for the synthesis of cellulose nanofiber (CNF). Cellulose nanofiber is a nano-sized cellulose material that has unique physical and mechanical properties. The synthesis was performed using a strong acid method with sulfuric acid. Sulfuric acid removes the amorphous region of cellulose so that the crystalline part can be isolated. CNF yield measurement showed that temperature, time, acid concentration, and interaction between each factor were affecting significantly to CNF yield. The result showed that yield of 14.98 grams, was obtained by hydrolysis at 35°C for 6 hours and 55% acid concentration. The crystallinity measurement showed that the temperature, time, acid concentration, and interaction between each factor during hydrolysis were not affected significantly to percent value of CNF crystallinity. The result showed that 31.1% of crystallinity, was obtained by hydrolysis at 45°C for 3 hours and 55% of acid concentration. The size measurement showed that the temperature, time, acid concentration and interaction between each factor were affected significantly. The result showed 894.25 nm as the best result, obtained by hydrolysis with 35°C and 60% acid concentration for 6 hours. CNF color was white with the best dispersion of hydrolysis at 35°C of 55% for 6 hours.